Copyright Protection for Creators of Digital Artwork - Deniesa, Salsabilla; Putri, Dela Rinanda; Amrullah, Arqam; Farid, AdrianaMaisarah binti Mohd; Hassan, Nor Audra Diana binti Md (Universitas Muhammadiyah Yogyakarta, 2021)
The development of digital technology can be a double-edged knife for the creative industry. It is undeniable that the ease of obtaining anything from internet can lead to a new problem, one of which is copyright infringement. Copyright of digital artworks should be protected since without which it will harm the rights of art workers who upload their works in the internet. The purpose of this research is to discuss and understand the copyright protection for digital artworks as well as some legal remedies that can be taken against infringement of the exclusive rights of the creators. This normative legal research employs statutory and comparative approach. The study shows that although legal protection for digital artworks has been governed under the Copyright Act 2014 (Law Number 28 of 2014 on Copyright), however its implementation but is still lacking and therefore improvement is necessary. In addition, the awareness of art workers about their rights should also be encouraged.